Pengaruh Kompetensi Terhadap Kinerja Guru Melalui Disiplin Kerja pada SMK Negeri 1 Cikarang Barat - Aulia Indah Mutiara; Supardi Supardi; Agus Dharmanto (Universitas 45 Surabaya, 2024)
This research aims to find out whether Competency has an effect on Teacher Performance through Work Discipline. The method used in this research is a quantitative method. The population in this study were teachers at SMK Negeri 1 Cikarang Barat. Determining the sample in this study used a saturated sampling technique, namely the entire number filled in was used as a sample of 106 teachers. Data were analyzed using SPSS 26. The methods used were validity test, reliability test, normality test, t test, and path analysis test. The research results show that competence influences teacher performance, competency influences work discipline, work discipline influences teacher performance. The results of the path analysis test show that competency influences teacher performance through work discipline at SMK Negeri 1 Cikarang Barat.